Functional sequence zones and Slavic L>T>N participles (preprint) - Taraldsen Medova, Lucie; Wiland, Bartosz (New York: Oxford University Press, 2018)
We make a case for morphemes as zones of functional sequence (‘fseq zones’) in Nanosyntax. Under such an approach, morphemes which compete for insertion with each other form the same fseq zone, while morphemes which co-occur together form different fseq zones. We illustrate this on the basis of the participle zone that is projected on top of verb stems in Slavic languages. We argue that in Polish and Czech, this participle zone spells out as L, T, or N, depending on its size and internal constituent structure. The constituent structure of this zone provides a direct solution to the long-standing puzzle in Polish and Czech morphology, namely why only unaccusative verbs built adjectival L-passives while all types of verbs build active L-participles.
Keywords: nanosyntax; participles; unaccusative; unergative; fseq zone; spell-out